Analisis Instrumen Evaluasi Pada Kurikulum Merdeka di SDN Polisi 1 Kota Bogor - Maisaroh, Siti; Irdiyansyah, Iyan; Hikmah, Nur (Innovative: Journal Of Social Science Research, 2025)
This research aims to analyze what evaluation instruments are dominantly used in the independent curriculum at SDN Police 1 Bogor City. This type of research is descriptive qualitative research. The subjects in this research were teachers, principals, and deputy principals in the curriculum field. Data collection uses triangulation, a combination of information between the results of observations, interviews, and documentation. Data analysis techniques include data collection, reduction, presentation, and conclusions. Based on the results of research studies, the independent curriculum's evaluation instrument is carried out according to the curriculum's characteristics, namely student-centered learning where assessments will be carried out according to the students' needs and abilities. Of the many evaluation instrument techniques used by teachers in schools with independent curricula dominantly, non-test instruments are (observation and interviews) because these instruments can describe student character.